Carcinogenic aristolochic acids upon activation by DT-diaphorase form adducts found in DNA of patients with Chinese herbs nephropathy - Stiborová, Marie; Frei, Eva; Sopko, Bruno; Wiessler, Manfred; Schmeiser, Heinz H (Carcinogenesis, 2002)
Aristolochic acid (AA), a naturally occurring nephrotoxin and rodent carcinogen, has recently been associated with the development of urothelial cancer in humans. Understanding which enzymes are involved in AA activation and/or detoxication is important in the assessment of an individual susceptibility to this natural carcinogen. We examined the ability of enzymes of rat renal and hepatic cytosolic fractions to activate AA to metabolites forming DNA adducts by the nuclease P1-enhanced version of the (32)P-postlabeling assay. Cytosolic fractions of both these organs generated AA-DNA adduct patterns reproducing those found in renal tissues from humans exposed to AA. 7-(Deoxyadenosin-N(6)-yl)aristolactam I, 7-(deoxyguanosin-N(2)-yl)aristolactam I and 7-(deoxyadenosin-N(6)-yl)aristolactam II were identified as AA-DNA adducts formed from AAI and 7-(deoxyguanosin-N(2)-yl)aristolactam II and 7-(deoxyadenosin-N(6)-yl)aristolactam II were generated from AAII by hepatic cytosol. Qualitatively the same AA-DNA adduct patterns were observed, although at lower levels, upon incubation of AAs with renal cytosol. To define the role of cytosolic reductases in the reductive activation of AA, we investigated the modulation of AA-DNA adduct formation by cofactors, specific inducers or selective inhibitors of the cytosolic reductases, DT-diaphorase, xanthine oxidase (XO) and aldehyde oxidase. The role of the enzymes in AA activation was also investigated by correlating the DT-diaphorase- and XO-dependent catalytic activities in cytosolic sample with the levels of AA-DNA adducts formed by the same cytosolic sample. On the basis of these studies, we attribute most of the cytosolic activation of AA to DT-diaphorase, although a role of cytosolic XO cannot be ruled out. With purified DT-diaphorase, the participation of this enzyme in the formation of AA-DNA adducts was confirmed. The binding orientation of AAI in the active site of DT-diaphorase was predicted by computer modeling based on published X-ray structures. The results presented here are the first report demonstrating a reductive activation of carcinogenic AAs by DT-diaphorase.
Keywords: karcinogeny; Liver; Phenanthrenes; buněčné jádro; Dose-Response Relationship, Drug; Rats; vztah mezi dávkou a účinkem léčiva; játra; Models, Molecular; léky rostlinné čínské; DNA, Complementary; xanthinoxidasa; DNA; Time Factors; kyseliny aristolochové; DNA Adducts; NAD(P)H Dehydrogenase (Quinone); Rats, Wistar; Aristolochic Acids; Chromatography, High Pressure Liquid; NAD(P)H dehydrogenasa (chinon); Antineoplastic Agents; vysokoúčinná kapalinová chromatografie; krysa rodu Rattus; Xanthine Oxidase; Aldehyde Oxidase; Enzyme Activation; Cell Nucleus; chemické modely; nefritida; fenantreny; molekulární modely; aldehydoxidoreduktasy; aldehydoxidasa; protinádorové látky; zvířata; cytosol; komplementární DNA; Cytosol; Carcinogens; časové faktory; aktivace enzymů; Thymus Gland; Models, Chemical; Aldehyde Oxidoreductases; potkani Wistar; thymus; adukty DNA; Drugs, Chinese Herbal; Nephritis; Animals